2021
DOI: 10.1002/ijch.202100052
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Property Relationships and Idiosyncrasies of Bulk, 2D Hybrid Lead Bromide Perovskites

Abstract: Bulk, 2D hybrid lead bromide perovskites comprise a robust family of halide perovskites with a rich structural and photophysical chemistry witnessed thus far. In an attempt to boost focus on systematically charting the phase space of 2D lead bromide perovskites, it is timely and critical to review the structure-property relationships that are emerging in this family of materials. In this review, we assess the multitude of (100)-orientated lead bromide perovskites, as well as the idiosyncratic (110)-orientated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 267 publications
0
26
0
Order By: Relevance
“…Unfortunately, the possibilities to tune their properties by changing chemical composition are very limited since only three organic cations, i.e., methylammonium (MA + ), formamidinium (FA + ), and MHy + , allow the construction of 3D lead halide perovskite structures. Furthermore, 3D perovskites suffer from low resistance to moisture and a weak photoluminescence quantum yield (PLQY) due to small exciton binding energy. , These drawbacks can be reduced by decreasing dimensionality. Furthermore, the layered structure with its lower symmetry may combine novel highly anisotropic functional properties, such as ferroelectricty , or NLO properties. ,, Therefore, a lot of efforts were undertaken in recent years to fabricate 2D HOIPs by employing various organic cations. Perhaps, the most widely used are RNH 3 + cations, where R is an alkyl or aromatic moiety. In these 2D perovskites, the inorganic layers separated by large organic cations interact with each other through weak van der Waals forces. They form, therefore, natural quantum wells and this feature brings unique properties, such as the large exciton binding energy and efficient PL. It is worth noting that there is also a group of 2D HOIPs, in which the separation between the inorganic layers is much smaller.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the possibilities to tune their properties by changing chemical composition are very limited since only three organic cations, i.e., methylammonium (MA + ), formamidinium (FA + ), and MHy + , allow the construction of 3D lead halide perovskite structures. Furthermore, 3D perovskites suffer from low resistance to moisture and a weak photoluminescence quantum yield (PLQY) due to small exciton binding energy. , These drawbacks can be reduced by decreasing dimensionality. Furthermore, the layered structure with its lower symmetry may combine novel highly anisotropic functional properties, such as ferroelectricty , or NLO properties. ,, Therefore, a lot of efforts were undertaken in recent years to fabricate 2D HOIPs by employing various organic cations. Perhaps, the most widely used are RNH 3 + cations, where R is an alkyl or aromatic moiety. In these 2D perovskites, the inorganic layers separated by large organic cations interact with each other through weak van der Waals forces. They form, therefore, natural quantum wells and this feature brings unique properties, such as the large exciton binding energy and efficient PL. It is worth noting that there is also a group of 2D HOIPs, in which the separation between the inorganic layers is much smaller.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the type and energy of emissions both depend on the crystal structure. In this respect, three different types of PL are recognized in lead halide perovskites, i.e ., broadband PL with a large Stokes shift assigned to self-trapped excitons (STEs), relatively narrow PL with a small Stokes shift due to bound excitons (BEs), and a narrow PL explained by free excitons (FEs). ,, Narrow PL attributed to FE and BE states is typically observed for 3D perovskites and 2D analogues with the crystallographic orientation ⟨100⟩, , while broadband STE-related PL often occurs in corrugated 2D structures (⟨110⟩ and ⟨111⟩), , as well as in 1D and 0D structures. , However, PL related to STE states can also be observed for some ⟨100⟩-oriented perovskites. For instance, both FE- and STE-type PL was reported for (PMA) 2 PbBr 4 (PMA = phenylmethylammonium) and MHy 2 PbBr 4 . , …”
Section: Introductionmentioning
confidence: 99%
“…The quantum-well heterostructure of the 2D perovskite can be fine-tuned by chemical synthetic design through the number of the inorganic layers n and the organic “spacer” cation. Through the subsequent increase of the n- layer thickness in the 2D perovskite structure, the 2D materials’ optical and electronic properties ( E b , E g , and photoluminescence, PL) consecutively progress toward that of the 3D material. ,, Elseway, the organic spacer cation indirectly influences the structure of the inorganic framework through its resultant noncovalent templating, as well as the intrinsic chemical properties inherited to the material such as crystallinity, solubility, and thermochemical stability. Recently, the improved environmental stability of 2D hybrid lead iodide perovskites coupled with their inherent structural flexibility , enabled the fabrication of robust optoelectronic devices. , …”
Section: Introductionmentioning
confidence: 99%
“…The phase space of 2D halide perovskites has been populated by four primary structure subtypes, based on the charge of the organic spacer cation and the relative stacking of the inorganic layers: Ruddlesden–Popper (RP) structure (A′) 2 (A) n −1 M n X 3 n +1 , ,, Dion–Jacobson (DJ) structure (A′)­(A) n −1 M n X 3 n +1 , , alternating cations in the interlayer space (ACI) type (A′)­(A) n −1 M n X 3 n +1 and alkyl diammonium cations (NH 3 C m H m NH 3 )­(CH 3 NH 3 ) n −1 M n X 3 n +1 . Among these, the (100) RP layered halide perovskites are the most prevalent, as the majority of 2D perovskites published belong to this substructure family. ,,, , Less recurrent are layered perovskites of n ≥ 2, incorporating functional groups (e.g., unsaturated bonds, heteroatoms) within the organic layers that diversify significantly the explored phase space. , In this context, there are also n = 1 perovskites incorporating optical active organic layers that participate in the configuration of the optical properties of the 2D perovskite. Finally, 2D hybrid halide perovskites provide a viable architecture to perform small-molecule reactivity in the solid state by utilizing the chemical reactivity of functional organic layers to orchestrate covalent and noncovalent interactions for technological use, as in (photo)­polymerization, chemisorption, electrochemical ion cycling, etc., as well as small-molecule intercalation that has been achieved with the intercalation of neutral or polarizable molecules, affording a final material with distinct structural and/or electronic properties. , The inclusion of designer organic molecules with functional groups within the organic layers has been demonstrated to influence the optoelectronic and photophysical properties of 2D perovskite materials. , Previously, the Sargent group showed that the organic cation influences the quantum-well distribution, as 2D perovskite films and devices incorporating allylammonium (AA) resulted in superior ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation